HbA1c and Blood Pressure Correlation in Patients with Uncontrolled Type 2 Diabetes Mellitus - Gugun, Adang Muhammad; Suryanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The primary metabolic symptom of diabetes mellitus is hyperglycemia. Analysing HbA1c levels can help determine blood glucose management. Elevations in blood pressure can be caused by abnormalities in the metabolism of glucose. Patients with uncontrolled diabetes mellitus may experience elevated blood pressure. To ascertain whether blood pressure and HbA1c levels are correlated in patients with uncontrolled DM. There were 90 subjects aged between 31-65 years consisting of 48 men and 42 women. HbA1c levels were checked using the boronate affinity method and blood pressure was measured using a sphygmomanometer. Data analysis used the independent difference t-test and Mann-Whitney U test as well as the Spearman correlation test with a significance level of α=0.05. Research subjects had an average HbA1c level of 10 ± 2.08% (7.1-15). Mean systolic blood pressure was 132.75 ± 18.04 mmHg (90-180). The average diastolic blood pressure was 83.28 ± 10.38 mmHg (60-120). Subjects who experienced hypertension were 36.66%. There were no differences in blood pressure between men and women (systolic p=0.70 and diastolic p=0.58). There was no correlation between HbA1c levels and blood pressure (systolic: r=0.022, p=0.81 and diastolic: r=0.022, p=0.81). There was no correlation between duration of DM and blood pressure (systolic: r=.093 and p=0.38 and diastolic: r= -.032 and p=0.76). There was no correlation between HbA1c levels and blood pressure